Influence of blind loop on the pharmacokinetics of dopamine and sulfasalazine - Amnuay Thithapandha (2018)
Certain metabolic transformations of drugs occurring in animals can be attributed exclusively to the activity of the intestinal flora. These include the formation of meta-hydroxyphenylacetic acid (MHPAA) from dopamine and the release of sulfapyridine from sulfasalazine. The time of appearance of these metabolites in the urine after drug administration might reflect alterations in the host's bacterial flora as in bacterial overgrowth of the small intestine. In order to test this concept, self-filling blind loops were created in the jejuna of conventional rats. When dopamine (100 mg) was administered to both control and blind-loop animals, the ratio of MHPAA excreted in the first 24 hours to that in the second 24 hours averaged 12.2 (range 3.8 to 44) in animals with blind loops and 0.09 (range 0 to 0.16) in controls. The presence of a blind loop did not affect the excretion of homovanillic acid and dihydroxyphenylacetic acid, urinary metabolites of dopamine not derived from bacterial metabolism. Similar conclusion was also drawn from studies with sulfasalazine (10 mg). A significantly greater quantity of sulfapyridine was excreted in the first 6 hours in rats with blind loops than in controls. These studies indicate that the presence of a blind loop of the rat's small intestine is associated with significant alteration in the kinetics of urinary excretion of flora dependent metabolites of dopamine and sulfasalazine. This observation might serve as the basis for a new method of detecting bacterial overgrowth. © 1977 The Italian Pharmacological Society.